(untitled) (African Journal of Biomedical Research, 2023)
The antiplasmodial activities of Anacardium occidentale L. and Psidium guajava L. have been severally reported in literature. This present study aims to establish the efficacy of the methanol extracts of Anacardium occidentale L. and Psidium guajava L. leaves used for the treatment of acute malaria attack in Nigeria and its effect on the inhibition of β-haematin formation. The methanol extracts of leaves of Anacardium occidentale L. and Psidium guajava L. showed LD50 values >5000 mg/kg and 1600 mg/kg, respectively. On Day 4, comparable chemosuppression of parasitaemia of A. occidentale, 73.88 %; P. guajava, 72.75 % in infected mice (Plasmodium berghei. NK 65) at dose 100 mg/kg were obtained. However, both extracts had lower activities than chloroquine (83.58 %; 20 mg/mL). A. occidentale had a higher inhibition of formation of β haematin, the malaria parasite pigment, (IC50 of 36.1 ± 0.52 µg/mL) than P. guajava (IC50 of l0.25 ± 0.07 µg/mL) and chloroquine (IC50 of 2.71±0.39). The present study indicates that the antimalarial activities of methanol extracts of leaves of Anacardium occidentale L. and Psidium guajava L. are comparable and are linked to inhibition of β-haematin formation. The extract of Anacardium occidentale L. had higher inhibition of β-haematin formation than Psidium guajava L. which however, had additional mode of action suggested by the comparable in vivo.